2018
DOI: 10.1159/000491775
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-A and VEGF-B Coordinate the Arteriogenesis to Repair the Infarcted Heart with Vagus Nerve Stimulation

Abstract: Background/Aims: Vagus nerve stimulation (VNS) suppresses arrhythmic activity and minimizes cardiomyocyte injury. However, how VNS affects angiogenesis/arteriogenesis in infarcted hearts, is poorly understood. Methods: Myocardial infarction (MI) was achieved by ligation of the left anterior descending coronary artery (LAD) in rats. 7 days after LAD, stainless-steel wires were looped around the left and right vagal nerve in the neck for vagus nerve stimulation (VNS). The vagal nerve was stimulated with regular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 54 publications
0
36
0
Order By: Relevance
“…According to the published protocol 18 , MI model was prepared by ligating the left anterior descending coronary artery (LAD) of rats. Briefly, after anaesthetized with ketamine (50 mg/kg, i.p.)…”
Section: Animals MI Model and Vnsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the published protocol 18 , MI model was prepared by ligating the left anterior descending coronary artery (LAD) of rats. Briefly, after anaesthetized with ketamine (50 mg/kg, i.p.)…”
Section: Animals MI Model and Vnsmentioning
confidence: 99%
“…or atropine (Atrop, 10 mg/kg, i.p.) were performed 1 h (h) before VNS (six rats/group), as described previously 18 .…”
Section: Animals MI Model and Vnsmentioning
confidence: 99%
See 1 more Smart Citation
“…108 Autonomic imbalance has been shown to attenuate angiogenesis after MI, by decreasing α7nAChR. 110 In addition, AChE inhibitors have been shown to promote the expression of VEGF through the activation of α7nAChR after MI, 34 thus stimulating angiogenesis and reducing infarct size and improving cardiac function. 110 In addition, AChE inhibitors have been shown to promote the expression of VEGF through the activation of α7nAChR after MI, 34 thus stimulating angiogenesis and reducing infarct size and improving cardiac function.…”
Section: F I G U R E 3 Schematic Representation Of the Possible Mechamentioning
confidence: 99%
“…109 A previous study demonstrated, VNS increased the expression of vascular endothelial growth factor (VEGF)-A and VEGF-B and activated angiogenesis in the heart after MI through a P13K/Akt/specificity protein 1 (Sp1) signalling pathway. 110 In addition, AChE inhibitors have been shown to promote the expression of VEGF through the activation of α7nAChR after MI, 34 thus stimulating angiogenesis and reducing infarct size and improving cardiac function. 33,34 It is well-known that cardiac rupture is a severe complication which can occur after MI.…”
mentioning
confidence: 99%